Comparison of a Presbyopia-correcting supplementary intraocular lens combination and a capsular-bag lens: an in vitro study - Khoramnia, Ramin; Baur, Isabella; Yan, Weijia; Łabuz, Grzegorz; Auffarth, Gerd U. (Diagnostics, 2023)
We evaluated the optical quality of two approaches to trifocality: polypseudophakia versus monopseudophakia. The combination (polypseudophakia) of a monofocal Basis Z B1AWY0 and AddOn Trifocal A4DW0M intraocular lens (IOL) was compared to using one Basis Z Trifocal B1EWYN IOL, all from 1stQ GmbH. In both approaches, we measured modulation transfer function (MTF) and Strehl Ratio (SR) values at 3.0 and 4.5 mm pupil sizes. We determined the through-focus (TF) MTF at 25, 50 and 100 lp/mm for the 3 mm aperture. United States Air Force (USAF) target images were recorded. MTF measurement of the trifocal lens and the combined monofocal and trifocal AddOn IOL showed good performance at the far and near focus for the 3 mm aperture. For the 4.5 mm aperture the MTF improved for the far focus but decreased for the intermediate and near focus. TF MTF showed better contrast at the far focus for the polypseudophakic setup but at the expense of the efficiency at the near focus. However, the USAF chart images revealed only minimal differences between both approaches. The optical quality of the polypseudophakic approach was not affected by the presence of two IOLs instead of one and proved to be comparable with the performance of one capsular-bag-fixated trifocal IOL. Differences between the single vs. two-lens approach seen in the TF MTF analysis could be attributed to the optical design that varied between the trifocal models.
Gesehen am 07.06.2023